The relations between practice and theory of forward exchange - EINZIG, P. (PSL Quarterly Review, 2014)
Within the economic sphere of Forward Exchange theory a close relationship between theory and practice is essential. On the one hand is a highly intricate system, the immense variety of technical details of which cannot be mastered adequately without a thorough practical experience. On the other hand, is an important set of economic principals arising from the study of that system with all its manifold implications, which cannot be mastered adequately without being familiar with methods of theoretical analysis. Most foreign exchange dealers are not trained to grasp its theoretical aspects, while most academic economists fight shy of Forward Exchange. The author criticizes the shortcomings and defects on both sides, and stresses the need for closing the gap between theory and practice in forward exchange. JEL: F31